Potential Development of Hydrocarbon in Basement Reservoirs In Indonesia - Sunarjanto, D.; Widjaja, S. (Geological Agency, 2013)
DOI:Â 10.17014/ijog.v8i3.165Basement rocks, in particular igneous and metamorphic rocks are known to have porosity and permeability which should not be ignored. Primary porosity of basement rocks occurs as the result of rock formation. The porosity increases by the presence of cracks occurring as the result of tectonic processes (secondary porosity). Various efforts have been carried out to explore hydrocarbon in basement rocks. Some oil and gas fields proved that the basement rocks are as reservoirs which so far have provided oil and gas in significant amount. A review using previous research data, new data, and observation of igneous rocks in some fields has been done to see the development of exploration and basement reservoirs in Indonesia. A review on terminology of basement rock up till the identification of oil and gas exploration in basement rocks need to be based on the latest technology. An environmental approach is suggested to be applied as an alternative in analyzing the policy on oil and gas exploration development, especially in basement reservoirs.